Shariah Framework Based on Qualities of Shariah Scholars Towards Islamic Fatwa Shopping in Nigeria - Yakasai, Umar Musa; Muhamad, Tijjani (Institut Agama Islam Negeri Ponorogo, 2023)
This study examines the characteristics of Islamic scholars in issuing fatwas, highlighting concerns that financial institutions seek fatwas that align with their profit-driven motives and often contradict Islamic principles. Focusing on Nigeria, it assesses the qualifications of advisors and supervisors in Islamic financial institutions and examines their link to fatwa issuance. Gathering insights from 250 randomly selected Shariah scholars and students, the research employed structural equation modeling (SEM) for analysis. A 5-point Likert scale was used to assess the reliability of survey responses. The consistency of the data was verified using mean variance extracted, composite reliability, and Cronbach's alpha. SEM assessed the relationship between scholars' qualifications and fatwa issuance. The results underscored the importance of attributes such as knowledge, piety, sincerity, honesty, and legal responsibility in fatwa issuance. The results confirmed strong links between these attributes and fatwa issuance, reflecting broader concerns about fatwa shopping. The scope of the study was limited to Nigeria and focused on scholars' perceptions of fatwa shopping.